2020
DOI: 10.1111/anu.13005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary black soldier fly ( Hermetia illucens Linnaeus) pulp on growth performance, antioxidant capacity and intestinal health of juvenile mirror carp ( Cyprinus carpio var. specularis)

Abstract: This study was conducted to investigate whether dietary supplementation of black soldier fly (Hermetia illucens Linnaeus) pulp (BSFP) affects growth performance, antioxidant capacity and intestinal health of juvenile mirror carp (Cyprinus carpio var. specularis). A total of 270 juvenile mirror carp (13.68 ± 0.02 g) were randomly allotted to five dietary treatments, BSFP0, BSFP25, BSFP50, BSFP75 and BSFP100, in which BSFP was included in the basal diet at 0, 43.7, 87.3, 131 and 174.7 g/kg, respectively. Then, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 55 publications
7
33
0
Order By: Relevance
“…In the present study, plasma AST, ALT and CK levels were not affected by BSFL meal, suggesting that dietary BSFL meal might not affect liver and muscle health. In accordance with the present study, several studies demonstrated that the activities of serum ALT and AST were not altered or in some cases even decreased by dietary inclusion of BSFL meal or pulp in pre-smolt ( 32 ) and post-smolt salmon ( 9 ), Jian carp ( 72 ), Japanese seabass ( 69 ) and mirror carp ( 74 ). In addition, Belghit, Waagbø ( 32 ) and Vargas-Abúndez, Randazzo ( 78 ) observed that dietary inclusion of BSFL meal did not affect the expression of genes involved in stress response (heat‐shock protein‐70 and superoxide dismutase) in the liver of pre-smolt salmon and clownfish ( Amphiprion ocellaris ) respectively, suggesting no induction of stress response and further confirming that BSFL ingredients did not cause any negative effect on liver health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, plasma AST, ALT and CK levels were not affected by BSFL meal, suggesting that dietary BSFL meal might not affect liver and muscle health. In accordance with the present study, several studies demonstrated that the activities of serum ALT and AST were not altered or in some cases even decreased by dietary inclusion of BSFL meal or pulp in pre-smolt ( 32 ) and post-smolt salmon ( 9 ), Jian carp ( 72 ), Japanese seabass ( 69 ) and mirror carp ( 74 ). In addition, Belghit, Waagbø ( 32 ) and Vargas-Abúndez, Randazzo ( 78 ) observed that dietary inclusion of BSFL meal did not affect the expression of genes involved in stress response (heat‐shock protein‐70 and superoxide dismutase) in the liver of pre-smolt salmon and clownfish ( Amphiprion ocellaris ) respectively, suggesting no induction of stress response and further confirming that BSFL ingredients did not cause any negative effect on liver health.…”
Section: Discussionsupporting
confidence: 92%
“…Jian) ( 72 ), yellow catfish ( Pelteobagrus fulvidraco ) ( 73 ) and mirror carp ( Cyprinus carpio var. specularis) ( 74 ). However, Zhou, Liu ( 75 ) observed that serum antioxidant capacity was not affected by partial replacement of dietary fishmeal with BSFL meal in Jian carp, while complete replacement reduced serum antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the serum MDA content was decreased as with the increase of full-fatted BSFM inclusion due to the stronger activity of antioxidant enzymes in the defense system. Similar encouraging results have been confirmed in several fish species (31,32). It has been reported that antioxidant ability due to chitin appears to have a positive effect on the immune system of poultry, as it exhibits prebiotic properties in the large intestine and appears to exhibit a bacteriostatic effect on Gram-negative bacteria (33).…”
Section: Discussionsupporting
confidence: 71%
“…Our observation is in line with the opinion of Li et al (2017) and Fawole et al (2020) who found that CAT activities in fish increased when including HILM in their diets. Similarly, Xu et al (2020) showed that increasing HILM dietary content significantly increased plasma CAT activity and decreased MDA content of the juvenile mirror carp. Besides, we also found that the plasma oxidative metabolites were affected by the dietary treatments and showed decreased values of MDA as a result of the dietary inclusion levels of HILM.…”
Section: Discussionmentioning
confidence: 87%